Brightness and polarization scattering functions of different natures of asbestos in the visible and near infrared domain. (September 2020) - Renard, Jean-Baptiste; Duée, Cédric; Bourrat, Xavier; Haas, Hubert; Surcin, Jérémy; Couté, Benoit
Highlights: First scattering functions of asbestos. Low polarization with positive color effect from green to near infrared. Strong variability of brightness scattering function for different asbestos. Chrysotile is the darkest sample at scattering angle of 90°. Abstract: Asbestos refers to silicate minerals belonging to the serpentine group (chrysotile) and the amphibole group (crocidolite, amosite, tremolite-asbestos, anthophyllite-asbestos and actinolite-asbestos). Such materials have strong effect on health, and real-time instrumentation is on demand to detect asbestos. The current real-time techniques use only some aspects of the optical properties of asbestos, since the scattering properties (brightness and linear polarization scattering functions) of the various natures of asbestos has not been yet fully determined. We present here the brightness and linear polarization scattering functions for 6 natures of asbestos in the 425-1650 nm spectral domain obtained with the PROGRA2 instrument. Although the samples exhibit different shapes, the linear polarization values remain low, bell-shaped as usual for irregular particles, and close to those of mineral particles previously studied with PROGRA2. On the opposite, asbestos brightness curves present strong differences for the different samples. The chrysotile is darker than the other samples in the 80°-150° angle range, probably due to its tubular shape that can act as a light trap for scattering angles greater than a few tens of degrees. Other asbestos particles can be distinguished from building materials such as glass wool or plaster through their brightness curves in some scattering angle ranges. These new laboratory measurements indicate that the optical scattered properties could be used in the future to tentatively detect asbestos particles in a medium generated from building materials.